Transcranial Direct Current Stimulation (tDCS) Can Modulate EEG Complexity of Children With Autism Spectrum Disorder - Kang, Jiannan; Cai, Erjuan; Han, Junxia; Tong, Zhen; Li, Xin; Sokhadze, Estate M.; Casanova, Manuel F.; Ouyang, Gaoxiang; Li, Xiaoli (Frontiers in Neuroscience, 2018)
Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental disorder which affects the developmental trajectory in several behavioral domains, including impairments of social communication, cognitive and language abilities. Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique, and it was used for modulating the brain disorders. In this paper, we enrolled thirteen ASD children (11 males and 2 females; mean±SD age: 6.5±1.7 years) to participate in our trial. Each patient received 10 treatments over the dorsolateral prefrontal cortex (DLPFC) once every two days. Also, we enrolled thirteen ASD children (11 males and 2 females; mean±SD age: 6.3±1.7 years) waiting to receive therapy as controls. A maximum entropy ratio (MER) method was adapted to measure the change of complexity of EEG series. It was found that the MER value significantly increased after tDCS. This study suggests that tDCS may be a helpful tool for the rehabilitation of children with ASD.